Differential expression of Notch related genes in dental pulp stem cells and stem cells isolated from apical papilla - Damrong Damrongsri; Nunthawan Nowwarote; Opor Sonpoung; Suphalak Photichailert; Thanaphum Osathanon (Elsevier, 2021)
Although dental pulp and apical papilla are originated from neural crest cells, these tissues exhibit distinct characteristics. Notch signaling is one of the known signaling pathways regulating stemness and behaviors of stem cells. The aim of this study was to examine Notch signaling related gene expression profile comparing between coronal pulp tissues and apical pulp complex. Results demonstrated that coronal pulp tissue had higher expression levels of various genes in Notch pathway. However, NOTCH2, MAML2, DTX4, and NEDD4 mRNA levels were significantly lower in coronal pulp tissue than those of apical pulp complex. Furthermore, dental pulp stem cells (DPSCs) and stem cells isolated from apical papilla (SCAPs) were isolated and characterized. These two cell types exhibited similar mesenchymal stem cell surface markers. DPSCs expressed higher mRNA levels of NOTCH3, NOTCH4, DLL1, and HES1. In addition, SCAPs demonstrated higher colony formation and cell proliferation than DPSCs. In summary, cells and tissues from dental pulp and apical papilla exhibited the distinct gene expression profile of Notch related genes. This could be of one the signaling participated in control of DPSCs and SCAPs cells behaviors.